Accurate Modeling and Analysis of Isolation Performance in Multiport Amplifiers - Marinella Aloisio; Piero Angeletti; Salvatore D'Addio (Active and Passive Electronic Components)
A Multiport Amplifier (MPA) is an implementation of the satellite power amplification section that allows sharing the payload RF power among several beams/ports and guarantees a highly efficient exploitation of the available DC satellite power. This feature is of paramount importance in multiple beam satellite systems where the use of MPAs allows reconfiguring the RF output power among the different service beams in order to handle unexpected traffic unbalances and traffic variations over time. This paper presents Monte Carlo simulations carried out by means of an ESA in-house simulator developed in Matlab environment. The objective of the simulations is to analyse how the MPA performance, in particular in terms of isolation at the MPA output ports, is affected by the amplitude and phase tracking errors of the high power amplifiers within the MPA.